Preserving the Traditions of Easter Eggs in the Education of Children of the Highlands - Poyasyk, Oksana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
Nowadays the problem of spiritual revival of society is acute. Welfare in general depends on the spirituality of each of us. Spiritual and cultural level determines the strength of the nation. One of the most important tasks of spiritual education is to cultivate the sense of belonging to the people, traditions, art and history. It begins not only with mother's lullaby, parental word, granny’s tales, folk songs, proverbs, riddles, but with the subjects of folk art, which provide wisdom of ancestors and human values. Folk art provides an excellent basis for the development of culture. It all passes, generations are dying, everything is turned into ashes; only the spirit of the nation remains embodied in the works of folk art.